Superman : lost - Priest, Christopher J. (Christopher James), 1961-; Pagulayan, Carlo (DC Comics, 2024)
"When a routine Justice League mission goes awry, Superman must make a 20 year journey home. But he feels like a stranger when he returns to a world where no time has passed at all. After Superman is called away on a routine Justice League mission, Lois Lane awakens to find a complete stranger standing in her living room. The Man of Steel, home much sooner than expected, reveals he has, in fact, been lost in space for 20 years. Nothing and no one seem familiar to him anymore. The timeless bond between them has been severed...or has it? Can love conquer all? As Superman struggles to re-enter his life on Earth, follow the story of his epic 20-year Odyssey home"--